Alarmin S100A8 Activates Alveolar Epithelial Cells in the Context of Acute Lung Injury in a TLR4-Dependent Manner - Chakraborty, Deblina; Zenker, Stefanie; Rossaint, Jan; Hölscher, Anna; Pohlen, Michele; Zarbock, Alexander; Roth, Johannes; Vogl, Thomas (Frontiers in Immunology, 2017)
Alveolar epithelial cells are an essential part of the respiratory barrier in lungs for gas exchange and protection against pathogens. Damage to alveolar epithelial cells occurs during lung injury and PAMPs/DAMPs have been shown to activate alveolar epithelial cells. However, their interplay as well as the mechanism of alveolar epithelial cells’ activation especially by the alarmin S100A8/A9 is unknown. Thus, our aim was to study the mechanism of activation of alveolar epithelial cells (type I and type II) by S100A8 and/or LPS and to understand the role of endogenous S100A8/A9 in neutrophil recruitment in the lung. For our studies, we modified a previous protocol for isolation and culturing of murine alveolar epithelial cells. Next, we stimulated the cells with S100A8 and/or LPS and analyzed cytokine/chemokine release. We also analyzed the contribution of the known S100-receptors TLR4 and RAGE in alveolar epithelial cell activation. In a murine model of lung injury we investigated the role of S100A8/A9 in neutrophil recruitment to lungs. S100A8 activates type I and type II cells in a dose- and time-dependent manner which could be quantified by the release of IL-6, KC and MCP-1. We here clearly demonstrate, that alveolar epithelial cells are activated by S100A8 via a TLR4 dependent pathway. Surprisingly, RAGE, albeit mainly expressed in lung tissue, plays no role. Additionally, we show that S100A8/A9 is an essential factor for neutrophil recruitment to lungs. We, therefore conclude that S100A8 promotes acute lung injury via Toll-like receptor 4-dependent activation of alveolar epithelial cells.